First-principles computational methods for quantum defects in two-dimensional materials: A perspective - Seo, Hosung; Ivady, Viktor; Ping, Yuan (American Institute of Physics, 2024)
Quantum defects are atomic defects in materials that provide resources to construct quantum information devices such as single-photon emitters and spin qubits. Recently, two-dimensional (2D) materials gained prominence as a host of quantum defects with many attractive features derived from their atomically thin and layered material formfactor. In this Perspective, we discuss first-principles computational methods and challenges to predict the spin and electronic properties of quantum defects in 2D materials. We focus on the open quantum system nature of the defects and their interaction with external parameters such as electric field, magnetic field, and lattice strain. We also discuss how such prediction and understanding can be used to guide experimental studies, ranging from defect identification to tuning of their spin and optical properties. This Perspective provides significant insights into the interplay between the defect, the host material, and the environment, which will be essential in the pursuit of ideal two-dimensional quantum defect platforms.